2021
DOI: 10.1039/d1na00180a
|View full text |Cite
|
Sign up to set email alerts
|

A porous PDMS pulsewave sensor with haircell structures for water vapor transmission rate and signal-to-noise ratio enhancement

Abstract: We present a porous polydimethylsiloxane (PDMS) pulsewave sensor with haircell structures that improves both water vapor transmission rate (WVTR) and signal-to-noise ratio (SNR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The high repeatability of resistance changes demonstrates the reliability of hydrogels as a wearable sensor (Figure S13, Supporting Information). The literature reports that increasing the contact area can effectively improve the SNR; [ 27 ] so, we calculated the SNR values of the wrinkled sensor based on the output signals of the limb motions (Figure S14, Supporting Information). The result indicated that the wrinkled hydrogel sensor has a considerable SNR value with a maximum of 5021, which lays the foundation for accurate monitoring of cardiac signals.…”
Section: Resultsmentioning
confidence: 99%
“…The high repeatability of resistance changes demonstrates the reliability of hydrogels as a wearable sensor (Figure S13, Supporting Information). The literature reports that increasing the contact area can effectively improve the SNR; [ 27 ] so, we calculated the SNR values of the wrinkled sensor based on the output signals of the limb motions (Figure S14, Supporting Information). The result indicated that the wrinkled hydrogel sensor has a considerable SNR value with a maximum of 5021, which lays the foundation for accurate monitoring of cardiac signals.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the pore size of 21 μm and the porosity of 45% at the weight ratio of 0.5:1 were selected. Further details are referenced in our previous study …”
Section: Resultsmentioning
confidence: 99%
“…Further details are referenced in our previous study. 37 Then, we considered higher moisture permeability than the skin perspiration level of 432 g/m 2 /day as the first design guideline for the chamber layer thickness. Four different porous PDMSs with thicknesses of 250, 300, 400, and 500 μm, which were greater than the chamber height of 100 μm, were fabricated for measurement of the water vapor transmission rate (WVTR).…”
Section: Design Of the Chamber Layer Materials And Thickness For High...mentioning
confidence: 99%
“…The laminated fabrics behave as porous membranes with WVTRs higher than the rate of transepidermal water loss (TEWL) of adult skin under normal conditions (5-10 g/h m 2 ) and within the range of TEWL during sweating (6-66 g/h m 2 ). Our samples also have WVTRs higher than those of non-porous 8 μm [54] and highly porous (45%) 40 μm [55] films of polydimethylsiloxane (5-6 and 20.3 g/h m 2 , respectively), which are elastomers commonly used in wearable devices. Therefore the data cumulatively suggest that fabric lamination with the adhesive film has a minimal blocking effect on moisture permeability.…”
Section: Air Permeability and Water Vapor Transmission Characterizationmentioning
confidence: 92%